MENINGKATKAN PROMOSI PARIWISATA MELALUI KONTEN DIGITAL YANG KREATIF PADA PEDAGANG DI SEPANJANG PANTAI WISATAKABUPATEN PANGANDARAN - Andri Asmari; Yusnaini, Kartijo, Nenden Handayani, Silvy Kartikasari (JOURNAL OF COMMUNITY DEDICATION, 2023)
This community service is carried out with the aim of providing understanding and additional insight to traders along the tourist coast of Pangandaran Regency about the importance of increasing tourism promotion in Pangandaran Regency through creative digital content to increase sales and income from the businesses they run. The priority problem encountered was a lack of understanding regarding how to promote using digital content because traders only sell face-to-face on the spot and rarely promote using online media, this affects their income. The implementation method in this research is Community Based Research, namely explanations from resource persons to traders. The method used in this activity is a meeting or face-to-face meeting between the resource person and traders along the tourist coast of Pangandaran Regency, where the resource person plays an important role in explaining various materials on how to increase tourism promotion through creative digital content so that their products can be introduced to the wider community. . The product resulting from this community service is that traders have accounts on social media and use them as a promotional tool by creating various creative digital content.